The Effect of Technology and Company Characteristics on Firm’s Survival: Case Study of Indonesian Manufacturing Industry - Aldizah Dajustia Hutami; Dyah Wulan Sari (MediaTrend, 2022)
Facing globalization and industrial revolution 4.0 requires companies to continue innovation to maintain their existences. Innovation can be carried out well if the company can absorb and apply the latest technology to increase the efficiency of its business. Firms that are unable to adapt to technology will not be able to compete with their counterparts. Therefore, this research was conducted to see the effect of technology, the firm's characteristics (size and location), and productivity (productivity and company profit) on the firm's survival. Using logistic regression, this study shows that technology, the firm's size, and productivity have a significant positive effect on the firm's survival. The location has a significant negative impact on the firm's survival, and profit does not significantly affect the firm's survival. The Hosmer and Lemeshow Test show that the model used in this study is fit for estimating all variables.